A method for preparing a water-based epoxy interface agent for tile paving
By modifying the synergistic effect of non-ionic self-emulsified aqueous epoxy resin, star-type branched polymer-linear aqueous epoxy curing agent and toughening agent, an aqueous epoxy interface agent for ceramic tile laying was prepared, which solved the problem of insufficient performance of the interface agent in the prior art and achieved high-performance ceramic tile laying effect.
Patent Information
- Application Number
- CN202411226453.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The existing ceramic tile interface agents have problems such as long solidification time, poor durability, weak bonding strength, weak crack resistance, and weak crack resistance, anti-permeability, chlorine salt corrosion, and weak freeze-thaw resistance.
By modifying the synergistic effect of non-ionic self-emulsified aqueous epoxy resin, star-type branched polymer-linear aqueous epoxy curing agent and toughening agent, an aqueous epoxy interface agent for ceramic tile laying is prepared to improve its anti-permeability, anti-chlorine salt corrosion, anti-freeze-thaw, anti-cracking and crack resistance, and enhance durability and bonding strength.
It has achieved water-based epoxy interface agent with anti-permeability, anti-chlorine salt corrosion, anti-freeze-thaw, crack resistance, strong crack resistance, good durability, short solidification time and high bonding strength, and is suitable for ceramic tile laying.
Smart Images

Figure CN119100698B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of interface agents, and in particular to a method for preparing a water-based epoxy interface agent for tile paving. Background Art
[0002] Ceramic tiles are widely used finishing materials for walls and floors. They have the advantages of low water absorption, high wear resistance, uniform size, acid resistance, and no radiation. Especially in the process of home decoration, ceramic tiles are economical, beautiful, and durable. At the same time, they are diverse in variety and can meet the needs of different levels and styles. People are accustomed to using ceramic tiles as decorative materials for bathrooms and kitchens. However, after traditional decoration construction, ceramic tiles are prone to loosening or even falling off, which poses a great safety hazard, not only causing serious economic losses, but also bringing the trouble of re-construction.
[0003] There are two main reasons for the falling of tiles: the first is due to the characteristics of tiles. Currently, high-quality tiles with good decorative effects, such as polished tiles or vitrified tiles, are more commonly used on the market. They are characterized by smooth surface and low water absorption. The water absorption rate is less than 0.1%, which causes the tiles to form an obvious interface and fall off during the pasting process; the second is due to tile adhesives. The currently widely used tile bonding method is still a direct mixture of cement and sand. For example, the widely used dry-laid base layer of cement: fine sand = 1:3 and the adhesive layer of cement: fine sand = 1:2, in which the cement is No. 325 cement. A small number of projects use special adhesive materials, but because the tiles are heavy and easy to sag during construction, their role in improving the interface needs further improvement.
[0004] In the prior art, there have been some reports on tile paving interface agents. For example, Chinese patent application with publication number CN107601985A discloses a tile interface agent, which includes a powder material and an aqueous material, and the powder material and the aqueous material are mixed at a weight ratio of 2.3:1 to 2.8:1. The tile interface agent has strong adhesion and weather resistance. Another example is Chinese patent application with publication number CN103496922A, which discloses a two-component tile interface agent for improving the interface performance and construction performance of tiles, including component A and component B, wherein component A includes: cement, quartz sand, metakaolin, and thickener; and component B includes: water reducer, toughening agent, penetrant, dispersant, defoamer, bactericide, accelerator, seasonal regulator, and water. This invention overcomes the problem of tile shedding caused by low water absorption and smooth interface of existing tiles, especially vitrified tiles. Although the above-mentioned tile interface agents all have corresponding advantages, they still have defects such as long setting time, poor durability, weak bonding strength, weak crack resistance and crack barrier performance, weak anti-penetration, resistance to chloride salt erosion, and anti-freeze-thaw performance, so they need to be improved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a water-based epoxy interface agent for tile paving. Through the innovation of the preparation process of the water-based epoxy interface agent, a water-based epoxy interface agent with strong anti-penetration, anti-chloride salt erosion, anti-freeze-thaw, anti-cracking, crack resistance, good durability, short setting time and high bonding strength can be obtained, which is particularly suitable for tile paving.
[0006] In order to realize the above technical solution, the present invention provides a method for preparing a water-based epoxy interface agent for tile paving, which specifically comprises the following steps:
[0007] S1. Preparation of modified nonionic self-emulsifying waterborne epoxy resin.
[0008] Add 80-90g of E51 bisphenol A epoxy resin and 3-8g of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane to a reactor equipped with a stirring and temperature control device, heat to 70-80°C, react for 1 hour, add 5-15g of polyethylene glycol diglycidyl ether, continue to keep warm and react for 1 hour to obtain a modified nonionic self-emulsifying waterborne epoxy resin for standby use;
[0009] S2. Preparation of curing agent,
[0010] S21, add 80-120g of E51 bisphenol A epoxy resin to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, control the reaction temperature to 65-75°C, stir at a speed of 300rpm, add the terminal amine polyether at a mass ratio of 1-2:1 to the reactor, and continue stirring for 2 hours until the reaction is complete to obtain an intermediate product; then add 50-100g of triethylenetetramine, and continue stirring for 1 hour at a temperature of 65-75°C and a stirring speed of 300rpm until the reaction is complete to obtain a linear waterborne epoxy curing agent;
[0011] S22. In a reactor equipped with a stirring device, a reflux and gas absorption device, a thermometer and nitrogen protection, a polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 2-4:1, and the mixture is reacted at a temperature of 120°C and a stirring speed of 300 rpm for 10 hours to obtain an intermediate product, a star-branched polymer I; 20-50 g of E51 bisphenol A epoxy resin and 80-100 g of polyethylene glycol are added to a reactor equipped with a stirring device, a reflux and drying device, a thermometer and nitrogen protection, and heated and stirred at a temperature of 100-120°C and a stirring speed of 300 rpm for 1 hour to remove After adding water, the temperature is adjusted to 90-100° C. and boron trifluoride etherate catalyst is added dropwise, and the reaction is continued for 4 hours to obtain an intermediate product, a star-branched polymer II, and the product is removed after cooling; 80-120 g of the star-branched polymer I is added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature is adjusted to 70° C. and the stirring speed is 300 rpm. The star-branched polymer II is heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1-2:1. After the dropwise addition is completed, the reaction is continued for 1 hour to obtain the final star-branched polymer;
[0012] S23, 80-120g of linear waterborne epoxy curing agent and 40-60g of star-branched polymer are added to a reactor equipped with a stirring device, a reflux device, and a thermometer, and stirred at 60-80°C at 300-600rpm, and 80-120g of deionized water is slowly added dropwise. The prepared self-emulsifying curing agent product is initially a milky white uniform emulsion, and then gradually becomes a transparent and clear viscous liquid to obtain a star-branched polymer-linear waterborne epoxy curing agent finished product, which is set aside;
[0013] S3. Preparation of toughening agent,
[0014] Mix nano-silicon dioxide and deionized water in a narrow-mouth flask at a mass ratio of 1:20, and stir at 70-80° C. and 300 rpm for 5 hours, replenishing the water lost by evaporation during the process to obtain a nano-silicon dioxide dispersion; mix the nano-silicon dioxide dispersion and γ-glycidyloxypropyltrimethoxysilane at a mass ratio of 1-2:1, and stir at room temperature and 300-600 rpm for 5 hours, then heat to 70-80° C. and continue to react for 1 hour, replenishing the water lost by evaporation during the process, and obtaining a toughening agent with a mass concentration of 4-8%, which is set aside;
[0015] S4, weigh 80-120g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1, 80-120g of the curing agent prepared in step S2, stir evenly, add 200-300g of the toughening agent with a mass concentration of 4-8% prepared in step S3, stir evenly again, then add 3000-4000g of silicate cement, 4000-5000g of river sand, 800-1000g of fly ash, 10-15g of water reducer, 5-10g of cellulose ether and 2000-3000g of water in sequence, and stir evenly at room temperature at 200-500rpm.
[0016] Preferably, in step S1, the amount of E51 bisphenol A epoxy resin added is 85 g, the amount of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane added is 5 g, and the amount of polyethylene glycol diglycidyl ether added is 10 g.
[0017] Preferably, in step S21, the amount of E51 bisphenol A epoxy resin added is 100 g, the reaction temperature is controlled to be 70° C., the stirring speed is 300 rpm, the terminal amine polyether is added to the reactor at a mass ratio of 1:1, and the amount of triethylenetetramine added is 70 g.
[0018] Preferably, in step S22, polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 3:1, and reacted for 10 hours at a temperature of 120° C. and a stirring speed of 300 rpm to obtain an intermediate product, a star-branched polymer I.
[0019] Preferably, in step S22, the amount of E51 bisphenol A epoxy resin added is 40 g, the amount of polyethylene glycol added is 90 g, and after heating and stirring at a temperature of 110° C. and a stirring speed of 300 rpm for 1 hour to remove water, the temperature is adjusted to 100° C. and boron trifluoride ether catalyst is added dropwise, and the reaction is continued for 4 hours to obtain an intermediate product, star-branched polymer II.
[0020] Preferably, in the step S22, 100 g of star-branched polymer I is added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature is adjusted to 70° C. and the stirring speed is 300 rpm. The star-branched polymer II is heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1:1. After the dropwise addition is completed, the reaction is continued for 1 hour to obtain the final star-branched polymer.
[0021] Preferably, in step S23, the amount of the linear waterborne epoxy curing agent added is 100 g, the amount of the star-branched polymer added is 50 g, and the amount of deionized water added is 100 g.
[0022] Preferably, in step S3, the mass ratio of the nano-silica dispersion to γ-glycidyloxypropyltrimethoxysilane is 1:1, and the mass concentration of the toughening agent is controlled to be 5%.
[0023] Preferably, in step S4, the amount of modified nonionic self-emulsifying waterborne epoxy resin added is 100 g, the amount of curing agent added is 100 g, the amount of toughening agent added is 220 g, the amount of silicate cement added is 3680 g, the amount of river sand added is 4600 g, the amount of fly ash added is 920 g, the amount of water reducer added is 11 g, the amount of cellulose ether added is 7 g, and the amount of water added is 2100 g.
[0024] The beneficial effects of the preparation method of a water-based epoxy interface agent for tile paving provided by the present invention are:
[0025] 1) The present invention innovates the overall preparation process of the water-based epoxy interface agent, and through the synergistic effect between the modified non-ionic self-emulsifying water-based epoxy resin, the star-branched polymer-linear water-based epoxy curing agent and the toughening agent, a water-based epoxy interface agent with strong anti-penetration, anti-chloride salt corrosion, anti-freeze and thaw, anti-cracking, crack resistance, good durability, short setting time and high bonding strength can be obtained, which is particularly suitable for tile paving.
[0026] 2) The present invention modifies the water-based epoxy resin and introduces the hydrophilic chain segment into the molecular chain of the epoxy resin or the curing agent by chemical grafting to form an etherified water-based epoxy resin. The etherified water-based epoxy resin is miscible with water in any proportion and can construct a synergistic coupling effect of epoxy resin polymerization and curing with cement hydration hardening in the cement concrete system, thereby providing better bonding performance, greater ductility and excellent durability. After hardening, it has good matching with the mechanical properties of the concrete matrix and can form a stable polymer network interpenetrating structure.
[0027] 3) The present invention innovatively designs the preparation process of the curing agent, introduces a polyether segment into E51 epoxy resin and a fatty amine compound to synthesize a non-ionic self-emulsifying waterborne epoxy resin curing agent, and comprises the addition of terminal amine polyether, triethylenetetramine and epoxy resin in a linear waterborne epoxy curing agent, and chemical grafting of polyethylene glycol, polyetheramine and other branches in a star-shaped branched polymer to the central molecule of 2,4,6-tris(dimethylaminomethyl)phenol, which can extend the branches of the star-shaped structure, further increase the branching degree, improve the water solubility and compatibility with the modified non-ionic self-emulsifying waterborne epoxy resin, and improve the curing performance of the epoxy resin space network, so that the non-ionic self-emulsifying waterborne epoxy resin curing agent and the modified non-ionic self-emulsifying waterborne epoxy resin prepared in step S1 have basically the same viscosity, active substance concentration (epoxy value, amine value) and curing time, and can shorten the cement hardening time after mixing with cement.
[0028] 4) The present invention adopts a hydrothermal method to prepare a nano-silica dispersion through an innovative design of the toughening agent preparation process, improves the dispersion effect of nano-silica particles, and adds siloxane molecules during the preparation process to form a toughening agent by a one-step synthesis method, which can simultaneously achieve the simultaneous enhancement of the organic and inorganic phases, is beneficial to stabilizing the network interpenetrating structure formed by the epoxy resin in the cement-based material, increases the chemical bonding and physical bite between the two, and increases the anti-cracking and crack-blocking properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary persons in the art without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A method for preparing a water-based epoxy interface agent for tile paving, specifically comprising the following steps:
[0033] S1, preparation of modified nonionic self-emulsifying waterborne epoxy resin, add 85g of E51 bisphenol A epoxy resin and 5g of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane into a reactor equipped with a stirring and temperature control device, heat to 75°C, react for 1 hour, add 10g of polyethylene glycol diglycidyl ether, continue to keep warm and react for 1 hour to obtain a modified nonionic self-emulsifying waterborne epoxy resin, and set aside;
[0034] S2. Preparation of curing agent,
[0035] S21, add 100g of E51 bisphenol A epoxy resin to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, control the reaction temperature to 70°C, stir at a speed of 300rpm, add the terminal amine polyether in a mass ratio of 1:1 to the reactor, and continue stirring for 2 hours until the reaction is complete to obtain an intermediate product; then add 70g of triethylenetetramine, and continue stirring for 1 hour at a temperature of 70°C and a stirring speed of 300rpm until the reaction is complete to obtain a linear waterborne epoxy curing agent;
[0036] S22. In a reactor equipped with a stirring device, a reflux and gas absorption device, a thermometer and nitrogen protection, a polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 3:1, and the mixture is reacted at a temperature of 120°C and a stirring speed of 300 rpm for 10 hours to obtain an intermediate product, a star-branched polymer I. In a reactor equipped with a stirring device, a reflux and drying device, a thermometer and nitrogen protection, 40 g of E51 type bisphenol A epoxy resin and 90 g of polyethylene glycol are added, and the mixture is heated and stirred at a temperature of 110°C and a stirring speed of 300 rpm for 1 hour to remove water. The temperature was adjusted to 100° C. and a boron trifluoride etherate catalyst was added dropwise, and the reaction was continued for 4 hours to obtain an intermediate product, a star-branched polymer II, and the product was removed after cooling; 100 g of the star-branched polymer I was added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature was adjusted to 70° C. and the stirring speed was 300 rpm. The star-branched polymer II was heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1:1. After the dropwise addition was completed, the reaction was continued for 1 hour to obtain the final star-branched polymer;
[0037] S23, 100g of linear waterborne epoxy curing agent and 50g of star-branched polymer are added to a reactor equipped with a stirring device, a reflux device, and a thermometer, and fully stirred at 500rpm at 70°C, and 100g of deionized water is slowly added dropwise. The prepared self-emulsifying curing agent product is initially a milky white uniform emulsion, and then gradually becomes a transparent and clear viscous liquid. The star-branched polymer-linear waterborne epoxy curing agent finished product is ready for use;
[0038] S3, preparation of toughening agent, nano silicon dioxide and deionized water are mixed in a narrow-mouth flask at a mass ratio of 1:20, and stirred at 80°C and 300rpm for 5 hours, and the water lost by evaporation is supplemented during the process to obtain a nano silicon dioxide dispersion, and the nano silicon dioxide dispersion and γ-glycidyloxypropyltrimethoxysilane are mixed at a mass ratio of 1:1, and stirred at room temperature and 500rpm for 5 hours, and then the temperature is raised to 80°C and the reaction is continued for 1 hour, and the water lost by evaporation is supplemented during the process to obtain a toughening agent with a mass concentration of 5%, which is set aside;
[0039] S4. Weigh 100 g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1 and 100 g of the curing agent prepared in step S2, stir evenly, add 220 g of the toughening agent with a mass concentration of 5% prepared in step S3, stir evenly again, then add 3680 g of silicate cement, 4600 g of river sand, 920 g of fly ash, 11 g of water reducer, 7 g of cellulose ether and 2100 g of water in sequence, and stir evenly at room temperature at 300 rpm.
[0040] Example 2
[0041] A method for preparing a water-based epoxy interface agent for tile paving, specifically comprising the following steps:
[0042] S1. Preparation of modified nonionic self-emulsifying waterborne epoxy resin.
[0043] Add 90g of E51 bisphenol A epoxy resin and 4g of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane to a reactor equipped with a stirring and temperature control device, heat to 75°C, react for 1 hour, add 6g of polyethylene glycol diglycidyl ether, continue to keep warm and react for 1 hour to obtain a modified nonionic self-emulsifying waterborne epoxy resin for standby use;
[0044] S2. Preparation of curing agent,
[0045] S21, add 120g of E51 bisphenol A epoxy resin to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, control the reaction temperature to 70°C, stir at a speed of 300rpm, add the terminal amine polyether in a mass ratio of 1:1 to the reactor, and continue stirring for 2 hours until the reaction is complete to obtain an intermediate product; then add 50g of triethylenetetramine, and continue stirring for 1 hour at a temperature of 70°C and a stirring speed of 300rpm until the reaction is complete to obtain a linear waterborne epoxy curing agent;
[0046] S22. In a reactor equipped with a stirring device, a reflux and gas absorption device, a thermometer and nitrogen protection, polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 3:1, and reacted at a temperature of 120°C and a stirring speed of 300 rpm for 10 hours to obtain an intermediate product, a star-branched polymer I; 50 g of E51 bisphenol A epoxy resin and 80 g of polyethylene glycol are added to a reactor equipped with a stirring device, a reflux and drying device, a thermometer and nitrogen protection, and heated and stirred at a temperature of 110°C and a stirring speed of 300 rpm for 1 hour to remove water, The temperature was adjusted to 100° C. and a boron trifluoride etherate catalyst was added dropwise, and the reaction was continued for 4 hours to obtain an intermediate product, a star-branched polymer II, and the product was removed after cooling; 100 g of the star-branched polymer I was added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature was adjusted to 70° C. and the stirring speed was 300 rpm. The star-branched polymer II was heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1:1. After the dropwise addition was completed, the reaction was continued for 1 hour to obtain the final star-branched polymer;
[0047] S23, 120g of linear waterborne epoxy curing agent and 60g of star-branched polymer are added to a reactor equipped with a stirring device, a reflux device, and a thermometer, and fully stirred at 500rpm at 70°C, and 120g of deionized water is slowly added dropwise. The prepared self-emulsifying curing agent product is initially a milky white uniform emulsion, and then gradually becomes a transparent and clear viscous liquid to obtain a star-branched polymer-linear waterborne epoxy curing agent finished product, which is set aside;
[0048] S3. Preparation of toughening agent,
[0049] Nano-silicon dioxide and deionized water are mixed in a narrow-mouth flask at a mass ratio of 1:20, and stirred at 80° C. and 300 rpm for 5 hours, during which the water lost by evaporation is supplemented to obtain a nano-silicon dioxide dispersion; the nano-silicon dioxide dispersion and γ-glycidyloxypropyltrimethoxysilane are mixed at a mass ratio of 1:1, and stirred at room temperature and 300-600 rpm for 5 hours, and then the temperature is raised to 80° C. and the reaction is continued for 1 hour, during which the water lost by evaporation is supplemented to obtain a toughening agent with a mass concentration of 5%, which is set aside;
[0050] S4. Weigh 100 g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1 and 100 g of the curing agent prepared in step S2, stir evenly, add 220 g of the toughening agent with a mass concentration of 5% prepared in step S3, stir evenly again, then add 3680 g of silicate cement, 4600 g of river sand, 920 g of fly ash, 11 g of water reducer, 7 g of cellulose ether and 2100 g of water in sequence, and stir evenly at room temperature at 300 rpm.
[0051] Example 3
[0052] In step S4, 80 g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1 and 120 g of the curing agent prepared in step S2 are weighed, and after stirring evenly, 200 g of the toughening agent with a mass concentration of 5% prepared in step S3 is added, and stirred evenly again, and then 3680 g of silicate cement, 4600 g of river sand, 1000 g of fly ash, 12 g of water reducer, 8 g of cellulose ether and 2200 g of water are added in sequence, and the mixture is fully stirred at 200-500 rpm at room temperature. The remaining steps are the same as those in Example 1.
[0053] Comparative Example 1
[0054] Step S1 is eliminated, and the E51 bisphenol A epoxy resin is not modified. In step S4, 100 g of the E51 bisphenol A epoxy resin is used to replace 100 g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1. The remaining steps are the same as those in Example 1.
[0055] Comparative Example 2
[0056] Step S2 is eliminated, and in step S4, 100 g of a Mannich base curing agent commercially available from Jiaxing Nanyang Wanshixing Chemical Co., Ltd. is used to replace the star-branched polymer-linear waterborne epoxy curing agent produced in step S2 of the present invention, and the remaining steps are the same as in Example 1.
[0057] Comparative Example 3
[0058] Step S2 is eliminated, no curing agent is added in step S4, and the remaining steps are the same as those in Example 1.
[0059] Comparative Example 4
[0060] Step S3 is eliminated. In step S4, 200 g of the nano-silicon dioxide dispersion with a mass concentration of 5% is used to replace 200 g of the toughening agent with a mass concentration of 5% prepared in step S3. The remaining steps are the same as those in Example 1.
[0061] Comparative Example 5
[0062] Step S3 is eliminated, and 200 g of the toughening agent with a mass concentration of 5% prepared in step S3 is not added in step S4. The remaining steps are the same as those in Example 1.
[0063] Comprehensive performance test of each embodiment product:
[0064] The water-based epoxy interface agent prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-5 was used for tile pasting. According to the test method of JC / T907-2002 "Concrete Interface Treatment Agent", the test was carried out at the concrete interface and the tile interface respectively. The test results of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1:
[0065] Table 1 Test data
[0066]
[0067] According to the experimental data in Table 1 above, it can be seen from the data in Example 1 and Comparative Example 1 that if the E51 bisphenol A epoxy resin is not modified and the E51 bisphenol A epoxy resin is directly used to replace the modified nonionic self-emulsifying waterborne epoxy resin prepared by the present invention, the surface drying time and the actual drying time of the finally prepared waterborne epoxy interface agent are not much different, but the shear bond strength and the tensile bond strength are greatly reduced. The possible reason is that the present invention modifies the waterborne epoxy resin and introduces the hydrophilic chain segment into the molecular chain of the epoxy resin or the curing agent by chemical grafting to form an etherified waterborne epoxy resin. The etherified waterborne epoxy resin is miscible with water in any proportion, and the coupling effect of epoxy resin polymerization curing and cement hydration hardening can be constructed in the cement concrete system, thereby providing better bonding performance, greater ductility and excellent durability. After hardening, it has good matching with the mechanical properties of the concrete matrix and can form a stable polymer network interpenetrating structure, thereby enhancing the shear bond strength and tensile bond strength after the tiles are laid.
[0068] By comparing the data in Example 1 and Comparative Examples 2-3, it can be seen that the addition of the curing agent has a great influence on the surface drying time and the actual drying time, and the curing agent prepared by the method of the present invention can shorten the surface drying time by 18 minutes and the actual drying time by 1.4 hours relative to the commercially available Mannich base curing agent (currently a relatively excellent curing agent on the market). The possible reason is that the present invention innovatively designs the preparation process of the curing agent, introduces the polyether segment into the E51 type epoxy resin and the fatty amine compound to synthesize and prepare the nonionic self-emulsifying waterborne epoxy resin curing agent, and the nonionic self-emulsifying waterborne epoxy resin curing agent includes the linear waterborne epoxy curing agent The addition of terminal amine polyether, triethylenetetramine and epoxy resin, and the chemical grafting of polyethylene glycol, polyetheramine and other branches in the star-branched polymer to the central molecule of 2,4,6-tris(dimethylaminomethyl)phenol can extend the branches of the star-shaped structure, further increase the branching degree, improve the water solubility and compatibility with the modified non-ionic self-emulsifying waterborne epoxy resin, and improve the curing performance of the epoxy resin space network, so that the non-ionic self-emulsifying waterborne epoxy resin curing agent and the modified non-ionic self-emulsifying waterborne epoxy resin prepared in step S1 have basically the same viscosity, active substance concentration (epoxy value, amine value) and curing time, and can shorten the cement hardening time after mixing with cement.
[0069] From the data of Example 1 and Comparative Examples 4-5, it can be seen that the addition of the toughening agent has a great influence on the shear bond strength, tensile bond strength and the bond failure area with concrete (which is a concrete manifestation of anti-cracking and crack-blocking performance. The better the anti-cracking and crack-blocking performance, the smaller the bond failure area). From the data of Comparative Examples 4 and 5, it can be seen that the present invention, through the innovative design of the toughening agent preparation process, adopts a hydrothermal method to prepare the nano-silicon dioxide dispersion, improves the dispersion effect of the nano-silicon dioxide particles, and adds siloxane molecules during the preparation process to form a toughening agent by a one-step synthesis method, which can simultaneously achieve the synchronous enhancement of the organic and inorganic phases, is beneficial to stabilize the network interpenetrating structure formed by the epoxy resin in the cement-based material, increase the chemical bonding and physical bite between the two, and increase the anti-cracking and crack-blocking performance.
[0070] It can be seen from the data of Examples 1-3 and Ratios 1-5 that the present invention, through the innovation of the overall preparation process of the water-based epoxy interface agent, can obtain a water-based epoxy interface agent with strong anti-penetration, anti-chloride salt erosion, anti-freeze-thaw, anti-cracking, crack resistance, good durability, short setting time and high bonding strength through the synergistic effect between the modified non-ionic self-emulsifying water-based epoxy resin, the star-branched polymer-linear water-based epoxy curing agent and the toughening agent, which is particularly suitable for tile paving.
[0071] The above description is only a preferred embodiment of the present invention, but the present invention should not be limited to the contents disclosed in the embodiment and the drawings, so any equivalent or modification completed without departing from the spirit disclosed in the present invention shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing a water-based epoxy interface agent for tile paving, characterized in that The specific steps include: S1. Preparation of modified nonionic self-emulsifying waterborne epoxy resin. Add 80-90g of E51 bisphenol A epoxy resin and 3-8g of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane to a reactor equipped with a stirring and temperature control device, heat to 70-80°C, react for 1 hour, add 5-15g of polyethylene glycol diglycidyl ether, continue to keep warm and react for 1 hour to obtain a modified nonionic self-emulsifying waterborne epoxy resin for standby use; S2. Preparation of curing agent, S21, add 80-120g of E51 bisphenol A epoxy resin to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, control the reaction temperature to 65-75°C, stir at a speed of 300rpm, add the terminal amine polyether at a mass ratio of 1-2:1 to the reactor, and continue stirring for 2 hours until the reaction is complete to obtain an intermediate product; then add 50-100g of triethylenetetramine, and continue stirring for 1 hour at a temperature of 65-75°C and a stirring speed of 300rpm until the reaction is complete to obtain a linear waterborne epoxy curing agent; S22. In a reactor equipped with a stirring device, a reflux and gas absorption device, a thermometer and nitrogen protection, a polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 2-4:1, and the mixture is reacted at a temperature of 120°C and a stirring speed of 300 rpm for 10 hours to obtain an intermediate product, a star-branched polymer I; 20-50 g of E51 bisphenol A epoxy resin and 80-100 g of polyethylene glycol are added to a reactor equipped with a stirring device, a reflux and drying device, a thermometer and nitrogen protection, and heated and stirred at a temperature of 100-120°C and a stirring speed of 300 rpm for 1 hour to remove After adding water, the temperature is adjusted to 90-100° C. and boron trifluoride etherate catalyst is added dropwise, and the reaction is continued for 4 hours to obtain an intermediate product, a star-branched polymer II, and the product is removed after cooling; 80-120 g of the star-branched polymer I is added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature is adjusted to 70° C. and the stirring speed is 300 rpm. The star-branched polymer II is heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1-2:
1. After the dropwise addition is completed, the reaction is continued for 1 hour to obtain the final star-branched polymer; S23, 80-120g of linear waterborne epoxy curing agent and 40-60g of star-branched polymer are added to a reactor equipped with a stirring device, a reflux device, and a thermometer, and stirred at 60-80°C at 300-600rpm, and 80-120g of deionized water is slowly added dropwise. The prepared self-emulsifying curing agent product is initially a milky white uniform emulsion, and then gradually becomes a transparent and clear viscous liquid to obtain a star-branched polymer-linear waterborne epoxy curing agent finished product, which is set aside; S3. Preparation of toughening agent, Mix nano-silicon dioxide and deionized water in a narrow-mouth flask at a mass ratio of 1:20, and stir at 70-80° C. and 300 rpm for 5 hours, replenishing the water lost by evaporation during the process to obtain a nano-silicon dioxide dispersion; mix the nano-silicon dioxide dispersion and γ-glycidyloxypropyltrimethoxysilane at a mass ratio of 1-2:1, and stir at room temperature and 300-600 rpm for 5 hours, then heat to 70-80° C. and continue to react for 1 hour, replenishing the water lost by evaporation during the process, and obtaining a toughening agent with a mass concentration of 4-8%, which is set aside; S4, weigh 80-120g of the modified nonionic self-emulsifying waterborne epoxy resin prepared in step S1, 80-120g of the curing agent prepared in step S2, stir evenly, add 200-300g of the toughening agent with a mass concentration of 4-8% prepared in step S3, stir evenly again, then add 3000-4000g of silicate cement, 4000-5000g of river sand, 800-1000g of fly ash, 10-15g of water reducer, 5-10g of cellulose ether and 2000-3000g of water in sequence, and stir evenly at room temperature at 200-500rpm.
2. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S1, the amount of E51 bisphenol A epoxy resin added is 85 g, the amount of 2-(3,4-epoxycyclohexyl)ethyltriethylsilane added is 5 g, and the amount of polyethylene glycol diglycidyl ether added is 10 g.
3. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S21, the amount of E51 bisphenol A epoxy resin added is 100 g, the reaction temperature is controlled to be 70° C., the stirring speed is 300 rpm, the terminal amine polyether is added to the reactor at a mass ratio of 1:1, and the amount of triethylenetetramine added is 70 g.
4. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S22, polyetheramine and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 3:1, and reacted for 10 hours at a temperature of 120° C. and a stirring speed of 300 rpm to obtain an intermediate product, a star-branched polymer I.
5. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S22, the amount of E51 bisphenol A epoxy resin added is 40 g, the amount of polyethylene glycol added is 90 g, and after heating and stirring at a temperature of 110° C. and a stirring speed of 300 rpm for 1 hour to remove water, the temperature is adjusted to 100° C. and boron trifluoride ether catalyst is added dropwise, and the reaction is continued for 4 hours to obtain an intermediate product, a star-branched polymer II.
6. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S22, 100 g of star-branched polymer I is added to a reactor equipped with a stirring device, a reflux device, a thermometer and nitrogen protection, and the temperature is adjusted to 70° C. and the stirring speed is 300 rpm. The star-branched polymer II is heated to 100° C. and added dropwise to the reactor containing the star-branched polymer I through a constant pressure dropping funnel at a mass ratio of 1:
1. After the dropwise addition is completed, the reaction is continued for 1 hour to obtain the final star-branched polymer.
7. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S23, the amount of the linear waterborne epoxy curing agent added is 100 g, the amount of the star-branched polymer added is 50 g, and the amount of deionized water added is 100 g.
8. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S3, the mass ratio of the nano-silicon dioxide dispersion to γ-glycidyloxypropyltrimethoxysilane is 1:1, and the mass concentration of the toughening agent is controlled to be 5%.
9. The method for preparing a water-based epoxy interface agent for tile paving according to claim 1, characterized in that: In the step S4, the amount of modified nonionic self-emulsifying waterborne epoxy resin added is 100 g, the amount of curing agent added is 100 g, the amount of toughening agent added is 220 g, the amount of silicate cement added is 3680 g, the amount of river sand added is 4600 g, the amount of fly ash added is 920 g, the amount of water reducer added is 11 g, the amount of cellulose ether added is 7 g, and the amount of water added is 2100 g.
Citation Information
Patent Citations
Double-component ceramic tile interface agent as well as preparation method and using method thereof
CN103496922A
Ceramic tile interface agent
CN107601985A
Ceramic tile joint mixture and preparation method thereof
CN107337403A
Penetrating type waterborne waterproof epoxy coating and preparation method thereof
CN107418372A